New decade of the Belt and Road Initiative: Strategic positioning of Serbia-China relations and opening of a new chapter - Lalić, Bojan; Filipović, Filip (Napredak, 2024)
This paper explores in detail the key concept of the Belt and Road Initiative, which represents a pillar of PR China’s foreign policy. The paper focuses especially on the analysis of Serbia’s strategic position in the new decade of the global initiative, highlighting the importance of deepening cooperation with PR China. In light of the challenges faced by Serbia, including pressures regarding the recognition of so-called Kosovo and joining anti-Russia sanctions, Serbia’s relations with the European Union, NATO, and leading Western countries are increasingly strained. Under such circumstances, it becomes an imperative for Serbia to search for new opportunities for development by boosting cooperation with China within the Belt and Road Initiative. This paper thoroughly analyses Serbia’s strategic position, stressing its significant contribution and the benefits of participating in the Belt and Road Initiative. Also, it explores the potential for deepening cooperation between PR China and the Republic of Serbia, focusing on five key pillars: political coordination, development of infrastructural links, promoting efficient trade, improving financial cooperation, and intensifying cultural exchange. Special emphasis is put on eight new campaigns that could further reinforce this cooperation in the new decade of the Initiative. Furthermore, from the aspect of developing talents and building an ecosystem, the paper announces a new direction of future development of Serbia-China relations, providing theoretical support and strategic guidance for intensifying cooperation between the two countries in the next decade of the Belt and Road Initiative.
Keywords: Belt and Road Initiative; Serbia; strategic positioning; Serbia-China relations